An exact block-based reanalysis method for local modifications. (1st October 2015) - Gao, Guoqiang; Wang, Hu; Li, Enying; Li, Guangyao
Highlights: An alternative reanalysis algorithm based on the block matrix is proposed. The modified stiffness is classified into influenced region, stationary region and an interface region between them. The main computational cost concentrates on the influenced region. Compared with popular reanalysis methods, it can achieve an accurate response for large modification with lower computation. Abstract: This paper presents an alternative reanalysis algorithm based on the block matrix to address problems with local modifications. In this method, the modified stiffness can be classified as three parts: influenced region, stationary region and an interface region between them. The main computation cost concentrates on the influenced region by this specific blocked strategy. Compared with popular reanalysis methods, the proposed method can achieve an accurate response for large modification with lower computation cost. Several practical engineering problems are analyzed and the results are exactly as that performed by full analysis.